Respuestas

2014-01-09T23:11:41+01:00

X3 + 8Y3 = (x + 2y)(x^2 - 2xy + 4y^2)
             
 Todas las otras responde a la forma
       a^3 - b^3 = (a - b)(a^2 + ab + b^2)
 Te hago la primera. Las otras las haces siguiendo la misma metodología                                                                                                       
27X3 - (1/27)Y3 = (3x - 1/3y)(9x^2 + x.y + (1/9)y^2
                           a = \sqrt[3]{27x^{3}}
                           b = \sqrt[3]{\frac{1}{27}y^{3}}